A scheme for capturing the kinetic energy of the flow liquid in a ship's cabin. (15th December 2022) - Li, Boyang; Zhang, Rui; Zhang, Baoshou; Deng, Fang; Cui, Ying
Abstract: The study proposes a solution for the energy capture of a sailing liquid cargo ship, which is essentially an organic combination of an Savonius turbine and a ship's rolling cabin. A model of the cabin turbine was simulated in ANSYS FLUENT from the perspective of the ship's roll and the rotor's rotational motion. Specifically, three cabin with opening lengths of 0.5, 1.0 and 1.5m were simulated to illustrate the sinusoidal trend of the axial velocity curves of the liquid at the cabin's opening position where the turbine is installed; When the burden of ship increases, the velocity at the opening decreases; when the burden is 90% and the ship's rolling angle is 20°, the peak axial velocity can reach 2.2 m/s, the average kinetic energy reaches 2.2 kJ and the flow rate reaches 1.38 m 3 /s. Then, the maximum values of the turbine's power coefficients are 0.21, 0.25 and 0.33 respectively, and their corresponding tip-speed rates are 1.0, 1.4 and 1.0. The torque coefficients decrease as the tip-speed rate increases. The velocity and pressure in the vicinity of the turbine present the non-stationary gradient images. Finally, the prediction of the power of turbine is discussed. Highlights: A combination of an Savonius turbine and a ship's rolling cabin is proposed. The velocity peak becomes higher with the ship's roll angle becomes larger. The maximum value of the turbine's power coefficient is 0.33 with TSR of 1.0. The pressure around the turbine presents the non-stationary gradient images.